FAKTOR-FAKTOR PENENTU KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (Studi Empiris pada Kecamatan Semarang Barat) - Ganjar Zamzam Budaya, 14.05.52.0289; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
The purpose of this research is to know the influence of the taxpayer's knowledge, the attitude of the taxpayer, the awareness of the taxpayer, the understanding of the taxpayer, the quality of service, the tax sanction on the taxpayer compliance of property tax in West Semarang Subdistrict.This research uses random sampling method in terms of sample selection. The criterion of sample selection is taxpayer who pay property tax in West Semarang Subdistrict. The data used are the primary data which are by giving questionnaire to the respondents. Questionnaires are processed as many as 100 respondents. The data obtained is analyzed using feasibility test instrument, classical assumption test, multiple linear regression and test of research model.The results of this study indicate that the attitudes, understanding and sanctions of taxpayers are positively affected to taxpayers’ compliance. However, knowledge and awareness of taxpayers are negatively affected to taxpayers’ compliance. On the other hand, quality of service does not show the positive effect to taxpayer’s compliance. Keywords: Knowledge, Attitude, Awareness, Understanding, Quality, Sanction and Taxpayer Compliance